Renewal in continuity - Pencarelli, Tonino; Cesaroni, Francesca Maria; Demartini, Paola (Piccola Impresa / Small Business, 2018)
Starting with issue 1/2018, with the change of its structure and the composition of its bodies, the journal Piccola Impresa/Small Business starts a process of profound renewal, in order to respond to the most recent scientific and editorial trends, yet remaining on the path of continuity and tradition. The main challenge is to make the journal a cultural reference platform–both in Italy and abroad–for all small business scholars. International diffusion, multidisciplinary approach, and quality are the main keywords of this process and the cornerstones of a path whose purpose is to improve the rating of the journal in the main national and international catalogues.